PASAR MODAL DAN PEREKONOMIAN INDONESIA: BIAYA KETERBUKAAN, PENGUNAAN DANA HASIL PENAWARAN UMUM, DAN PERAN PEMODAL ASING - Manurung, Roy M; Andriansyah, Andriansyah; Husodo, Bayu; Ngapon, Ngapon (Badan kebijakan Fiskal, 2012)
This paper summarizes the results of the last three years of research conducted by the Economic Research Division of the Indonesia Capital Market and Financial Institution Supervisory Agency (Bapepam-LK). The main topic of the research is related to the role of the capital market in the Indonesian economy, especially its role as the source of financing for business and as the alternative of investment for investors. The studies on the cost of disclosure, the use of IPO proceeds and the role of foreign investors will have special emphasizes.